Conversion of a standard direct expansion air conditioner to 100% outside air - Rojas Carbonero, José Luis (2007)
The present document is about the conversion of air conditioner standard equipment of direct expansion to an equipment 100% exterior air, for the operation emergency room of the National Hospital Guillermo Almenara Irigoyen. The hospital require for the operation rooms and emergency, enviroments totally aseptic (100% exterior air), and be the most economic possible due to attendance center budget limitations. To set up environment, it is available two kinds of equipments: 100% the especial exterior air and the converted standard. The select is based in the economic assessment method VAN. To convert the standard equipment require the selection of parts, modification and addition of some components, availability of employees qualify for the work and the confidence from the customer in engineering capacity for the installation and maintance if there is any. To achieve that aim it is propose a proceed logic and rational for the standard equipment conversion to an equipment 100% exterior air. Includes the start of the system, and the realization of essays for the temperature and relative humidity regulation until achieve the technical specifications require for the service.